Human Capital in the Knowledge Based Management - Ion PETRESCU (Revista de Management Comparat International)
All over the world, the problem of human capital acknowledge, it’s ways and means of shaping in order to improve it’s creative potential, tends to occupy a suitable place in the ensemble of all the organization’s management science and practice concerns. This study aims that, according to the theoretical ang pragmatical aquisitions, to present conceptual boundries about the human capital involvement in the knowledge based management. It starts with presenting the relations ballance and philosophy, and then there are being analysed the main growing factors of the human capital role in the knowledge based management. In the final part, there arebeing mentioned the human capital andit’s management, together with conclusions and recomendations.